The Encounter of the Divine with Human Realities in Exodus 15:22-25 (Hekima Review, 2016)
Exodus 15:22-25 can be read as an encounter of God with his people through ordinary events. Commonplace life events and occurrences are avenues through which God’s presence can be discerned. This encounter can lead humans to deepen their relationship with God. Covenant, in the form of rules or הָרוֹת (Torah), provided a context out of which God deepened his relationship with the people. The mediums through which God communicates himself to humans are symbolic. Exodus 15: 22-25 portrays how God uses a myriad of symbols to make himself present to a community of wayfarers who are tempted to doubt God’s company. Journey, water, covenant, and prophetic medium are some of the symbols explored in this exegesis.